European cities in the knowledge economy : the cases of Amsterdam, Dortmund, Eindhoven, Helsinki, Manchester, Munich, Münster, Rotterdam, and Zaragoza /: the cases of Amsterdam, Dortmund, Eindhoven, Helsinki, Manchester, Munich, Münster, Rotterdam, and Zaragoza. (2017) - Unknown
No abstract available